The extent to which the principles of the constructivist theory were included in Chemistry 1 curriculum for the first-grade secondary in Saudi Arabia - Alkhayrat, Afrah Mansour Hamoud (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the extent to which the principles of the constructivist theory were included in Chemistry 1 curriculum for the first-grade secondary in Saudi Arabia. The descriptive-analytical approach was used. The study population consisted of all pages of the Chemistry 1 course for the first secondary grade approved by the Ministry of Education in Saudi Arabia for the academic year 2021/2022, after excluding introductions and references, objectives, training issues and pages containing questions, definitions, summaries, standardized tests, or review of the lesson and chapter. The sample was represented in all units of Chemistry 1 course for the first secondary grade approved by the Ministry of Education in Saudi Arabia for the academic year 2021-2022 AD, which are: Introduction to chemistry, properties and changes, atom structure, chemical reactions, mole. The study tool consisted of (6) basic principles of constructivist theory and (15) indicators. The study concluded that: (growth is a basic principle in the social structure) is the first of the six principles, at a recurrence rate (of 250) times and a rate of (30.5%), while the principle of (social negotiation) was in the last rank out of six principles with a recurrence of (8) times and a percentage of (1%) in Chemistry course 1 for the first-grade of secondary school in Saudi Arabia. Considering the results, the study recommended a set of recommendations, most notably the necessity of increasing the inclusion of the principles of constructivist theory in Chemistry-1 curriculum for the first secondary grade in Saudi Arabia.